Advances in the management of early pregnancy loss. Issue 6 (December 2018) - Henkel, Andrea; Shaw, Kate A.
Abstract : Purpose of review: To describe recent advances in management of early pregnancy loss. Recent findings: Addition of mifepristone to current protocols for medical management of miscarriage increases effectiveness of a single dose of misoprostol and significantly reduces subsequent aspiration procedures. Women with an incomplete evacuation after medical management may be treated expectantly with similar rates of complete expulsion compared with surgical management at 6 weeks. As cytogenetic analysis improves, analysis of products of conception can be performed whether collected after surgical or medical management and is an efficient strategy in starting a recurrent pregnancy loss work-up. For those seeking pregnancy after miscarriage, conception immediately following an early pregnancy loss is not associated with increased risk of subsequent miscarriage. However, recent studies suggest that the original intendedness of the pregnancy resulting in miscarriage does not predict future reproductive goals of the woman, so family planning should be discussed at the time of miscarriage. Summary: Miscarriage is a common experience among reproductive-aged women and advances in medical management and modern-day aspiration techniques make the use of the sharp curette obsolete.